RESEARCH OF PRIORITY GOALS AND OBJECTIVES OF PHYSICAL EDUCATION LESSONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The goals of physical education lessons at school, which are reflected in the subjectstandard «Physical education» for grades 5-9 of general education organizations of the KyrgyzRepublic» , are perceived as an example, standard and model for measuring learning outcomes. Thearticle studied which goals, presented in the standard, are preferred by 9-grade students, parents,physical education teachers and future teachers, combined into four groups. Of the 14 goals, therespondents identified the most important and priority 7 goals, which were measured by assessingthe frequency repeatability and associated percentages. The obtained results showed that the goalsrelated to knowledge about physical culture are not assessed by a group of students as prioritycompared to the goals of motor skills development. It is recommended to pay special attention tothe development of spiritual values, as well as to knowledge about the healthy lifestyle of studentswhen determining the goals and objectives of physical education lessons, when preparing futureteachers, as well as when participating in sports events.
Keywords: school, physical education, standard, goal, priority direction, student, teacher, parent, assessment.